Better HPV prevention: a comprehensive review of Poland’s National Vaccination Strategy supplied with experts’ recommendations - Ledwoch, Justyna; Nitsch-Osuch, Aneta; Łosiowska, Anna; Biesiada, Aleksander; Mastalerz-Migas, Agnieszka; Magdziarz Ibrahim-El-Nur, Jakub; Bogdan, Magdalena (Family Medicine & Primary Care Review, 2025)
Human Papillomavirus (HPV) is a prevalent infection that is associated with many cancers, including cervical cancer. There are many types of HPV viruses, with types 16 and 18 associated with the majority of cervical cancer cases. Despite the fact that early detection programs and anti-HPV vaccinations were proven to be very effective, data suggests that only 11% of the Polish population participates in prevention programs. This report covers information on the Polish Ministry of Health’s Program against human papillomavirus vaccinations. The primary goal was to evaluate the program’s efficiency, to provide in-depth analysis of the strengths and weak-nesses of the program, and to identify factors with the strongest impact on improving vaccination rates. This paper also provides experts’ recommendations on potential improvements to the program. The paper is based on a comprehensive review of the current national vaccination strategy, including an analysis of vaccination coverage and the effectiveness of educational initiatives. It provides an in-depth analysis of annual statistics provided by Polish governmental institutions, including local governmental programs. Results indicate that re-moval of administrative barriers and locally oriented educational initiatives are crucial to improving vaccination rates. Recommendations suggest involving schools in the vaccination process, stressing the role of pharmacists in administering the vaccination, and creating a national notification system. The paper also identifies Polish involvement in worldwide anti-HPV initiatives like PERCH to increase vaccination coverage and reduce the number of HPV-related cancers. These strategies, if implemented could positively benefit public health status in Poland and decrease mortality and the number of cases of cervical cancer.